2021
DOI: 10.1002/smll.202103419
|View full text |Cite|
|
Sign up to set email alerts
|

Optimized Methodology for the Calculation of Electrostriction from First‐Principles

Abstract: In this work a new method for the calculation of the electrostrictive properties of materials using density functional theory is presented. The method relies on the thermodynamical equivalence, in a dielectric, of the quadratic mechanical responses (stress or strain) to applied electric stimulus (electric or polarization fields) to the strain or stress dependence of its dielectric susceptibility or stiffness tensors. Comparing with current finite‐field methodologies for the calculation of electrostriction, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…To proceed, we note that while one may consider electrostriction as the "strain/stress induced quadratically by an electric/polarisation field", one may also view it as the theromodynamically equivalent "linear change in susceptibility/inverse susceptibility induced by a stress or a strain" [9,10] shown below:…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To proceed, we note that while one may consider electrostriction as the "strain/stress induced quadratically by an electric/polarisation field", one may also view it as the theromodynamically equivalent "linear change in susceptibility/inverse susceptibility induced by a stress or a strain" [9,10] shown below:…”
mentioning
confidence: 99%
“…In our previous work [10], we outlined the advantages of this method of calculation, amongst which are greater computational efficiency and robustness. Viewed from the perspective of Eqs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies of electrostriction have also revealed interesting phenomena, such as the giant electrostriction [15][16][17][18][19][20][21][22][23][24][25], negative electrostriction [26,27], and deformations of liquid crystals [28,29] and biological cells [30]. On the theoretical side, electrostriction has also been under extensive study [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%